Environmental Impact Assessment Studies of Ground Water in Solapur Thermal Power Plant Area (Maharashtra), India - Joshi, M P; Barde, PV; Mungantiwar, PV; Bhole, AV; Devarkar, VD (Plantae Scientia, 2019)
Groundwater is a major source of drinking water in both urban and rural areas of Solapur. Solapur city is growing rapidly in terms of population, changing lifestyle and intense competition among users-agriculture, industry and domestic sectors is driving the groundwater to fall. Besides, the discharge of untreated wastewater through bores and leachate from unscientific disposal of solid wastes also contaminate groundwater, thereby reducing the quality of freshwater resources. In the work of Solapur, water samples were collected from around the villages in thermal power plant and water quality assessment was carried out from April 2015 & November 2015. The surface and groundwater characteristics have been established through analysis of water samples collected during the study area with respect to Physico-chemical characteristics and pollutant levels and the same has been compared with quality criteria for drinking water (IS: 10500). From the study, it is observed that the samples collected at all the 11 locations during pre-monsoon season are well within the prescribed limits laid by IS10500. We obtained fewer values in Post Monsoon are compared to Pre Monsoon season because of scanty rainfall.